1988
DOI: 10.1111/j.1528-1157.1988.tb03713.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐Up of 146 Children with Epilepsy after Withdrawal of Antiepileptic Therapy

Abstract: The relapse rate after discontinuation of antiepileptic drug treatment was investigated in 146 children with epilepsy, in whom medication was withdrawn according to a predesigned protocol, after a seizure-free period of at least 2 years and normalization of the EEG. The cumulative probability of remaining seizure-free in this series was 74.5%. Three-quarters of the relapses occurred during the withdrawal period and in the 2 years thereafter. From multivariate analysis, the factors indicating a significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
49
3
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 11 publications
7
49
3
2
Order By: Relevance
“…Seizure relapse rates after AEDs withdrawal have been reported as 22.4-40.0% and 85-90% of all those relapses that occur in the first two years of withdrawal [10][11][12][13][14][15]. Accordingly, children should be followed closely during the first two years after AEDs withdrawal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seizure relapse rates after AEDs withdrawal have been reported as 22.4-40.0% and 85-90% of all those relapses that occur in the first two years of withdrawal [10][11][12][13][14][15]. Accordingly, children should be followed closely during the first two years after AEDs withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…The most important point to withdraw antiepileptic drugs (AEDs) is the presence of a seizure free period of at least two years in an epileptic patient. The relapse rates in childhood-onset epilepsy have been reported as 22.4-40.0% after AEDs withdrawal [10][11][12][13][14]. Thus, determination of the risk factors for relapse after AEDs withdrawal is crucial to minimize the seizure relapse rates.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on these issues, and different risk factors for poor prognosis have been recognized (1)(2)(3)(4)(5)(6). Several studies have shown that children with neurological abnormalities or severe forms of epilepsy, such as infantile spasms (IS) or Lennox-Gastaut syndrome (LGS) have poor prognoses in terms of seizure control (3)(4)(5)(6)(7). Other risk factors related to outcome, such as seizure type, age at seizure onset, and EEG abnormalities, have been identified, but the results of earlier studies are not unanimous (1,(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Several studies have shown that children with neurological abnormalities or severe forms of epilepsy, such as infantile spasms (IS) or Lennox-Gastaut syndrome (LGS) have poor prognoses in terms of seizure control (3)(4)(5)(6)(7). Other risk factors related to outcome, such as seizure type, age at seizure onset, and EEG abnormalities, have been identified, but the results of earlier studies are not unanimous (1,(6)(7)(8)(9). In a Accepted December 19, 1996. Address correspondence and reprint requests to Dr. G. Braathen at Department of Pediatrics, Huddinge University Hospital, S-141 86 Huddinge, Sweden.…”
mentioning
confidence: 99%
“…Epilepsy is more commonly found in the hemiplegia and quadriplegia spastic type. [11][12] This study aimed to find the prevalence and risk factors of epilepsy in children with CP in Cipto mangunkusumo Hospital, Jakarta.…”
mentioning
confidence: 99%